PERAN PUBLIC RELATION DALAM PELAKSANAAN PROGRAM COORPORATE SOCIAL RESPONSIBILITY PADA PT. TELKOMSEL AMBON - RIDO DOMINGGUS LATUHERU (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
As PT Telkomsel's CSR Program also has the main commitments, namely: helping the community and providing optimal contributions to the community based on the 5 main pillars that are its CSR mission, namely: (1) building human capital; (2) Maintain social cohesion; (3) Strengthen economic value; (4) Encourage good government; and (5) Protecting the Environment.This is certainly inseparable from the intervention of the Public Relations (PR) department or other departments that carry out PR functions. At PT Telkomsel, PR is under the auspices of the Personnel department. PT Telkomsel Maluku can still